1991
DOI: 10.1002/j.1460-2075.1991.tb07737.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in the activity of a plant protein kinase.

Abstract: Bryophyllum fedtschenkoi is a Crassulacean acid metabolism plant whose phosphoenolpyruvate carboxylase is regulated by reversible phosphorylation in response to a circadian rhythm. A partially purified protein kinase phosphorylated phosphoenolpyruvate carboxylase in vitro with a stoichiometry approaching one per subunit and caused a concomitant 5‐ to 10‐fold decrease in the sensitivity of the carboxylase to inhibition by malate. The sites phosphorylated in vitro were identical to those phosphorylated in intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
143
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 29 publications
8
143
1
1
Order By: Relevance
“…To overcome this experimental limitation, chromatography on BDA was used to enrich for the tobacco leaf kinase. Previous experiments by Wang and Chollet (1993a) demonstrated that the tobacco enzyme, like C, (Bakrim et al, 1992;Wang and Chollet, 1993b) and CAM (Carter et al, 1991;Li and Chollet, 1994) PEPC-kinases, binds tightly to this "affinity" matrix and is eluted with buffered 0.5 M NaCl. Figure 1 depicts typical chromatographic elution profiles of tobacco PEPC-PK activity from a small column of BDA following extraction from illuminated or darkened leaves, ammonium sulfate concentration, and desalting.…”
Section: Light Activates Both Pepc-kinase and Pepc Activities In N-sumentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this experimental limitation, chromatography on BDA was used to enrich for the tobacco leaf kinase. Previous experiments by Wang and Chollet (1993a) demonstrated that the tobacco enzyme, like C, (Bakrim et al, 1992;Wang and Chollet, 1993b) and CAM (Carter et al, 1991;Li and Chollet, 1994) PEPC-kinases, binds tightly to this "affinity" matrix and is eluted with buffered 0.5 M NaCl. Figure 1 depicts typical chromatographic elution profiles of tobacco PEPC-PK activity from a small column of BDA following extraction from illuminated or darkened leaves, ammonium sulfate concentration, and desalting.…”
Section: Light Activates Both Pepc-kinase and Pepc Activities In N-sumentioning
confidence: 99%
“…therein). Finally, a protein phosphatase type 2A inhibitor such as microcystin-LR or okadaic acid should be included during enzyme extraction to minimize in vitro dephosphorylation of phosAs has been observed in C, and CAM leaves (Echevarria et al, 1990;Carter et al, 1991;Jiao et al, 1991a;Bakrim et al, 1992;Jiao and Chollet, 1992;Li and Chollet, 1994), the regulatory phosphorylation of PEPC in C, leaves from tobacco appears to be largely influenced by the activity state of PEPC-PK. However, a simultaneous assessment of the activity of the native PEPC-phosphatase heteromeric protein is necessary before a final conclusion can be drawn.…”
Section: Gin Is Involved In the Light Activation Of Tobacco-leaf Pepcmentioning
confidence: 99%
See 1 more Smart Citation
“…PEPc is activated at night by a phosphorylation event that is driven by a circadian clock. Circadian oscillations in the phosphorylation state of PEPc are due to circadian control of the expression and activity of PEPc kinase (PPCK; Carter et al, 1991;Hartwell et al, 1996Hartwell et al, , 1999Hartwell et al, , 2002. Phosphorylation reduces the sensitivity of PEPc to feedback inhibition by malate, and this makes phospho-PEPc more active in vivo at night, allowing malate to accumulate in the vacuole.…”
mentioning
confidence: 99%
“…The structural motif Lys/Arg-X-X-Ser of this phosphorylation site i~ also present at the corresponding position of the F. trinervia enzyme. Thus, this element is shared by the C4 and CAM isoforms but is lacking in the C:isoenzyme [3,18].…”
Section: Sequence Analysis Of Pcftppcl-1 and The Predictedmentioning
confidence: 99%